Distraksi Virtual Reality (VR) terhadap Tingkat Nyeri dan Cemas Anak Usia Sekolah yang Dilakukan Tindakan Invasif - Neneng Laelyana (Journal of Telenursing (JOTING), 2023)
This study aims to discover that healthcare technology has innovated in the quality and delivery of care to patients to motivate the promotion of safe, comfortable, and cost-effective care. The method used is a literature review from several online database searches using a research design in the form of a literature review. The results showed that from the six articles reviewed, several themes were obtained, namely 1) Virtual Reality for Pediatric Needle Procedural Pain: Two Randomized Clinical Trials, 2) A Systematic Review and Meta-analysis of virtual reality in Pediatrics: Effects on Pain and Anxiety, carried out meta-analysis, 3) Virtual reality distraction during pediatric intravenous line placement in the emergency department: A prospective randomized comparison study, 4). Virtual reality for pain and anxiety management in children, 5). Effect of an Immersive Virtual Reality Intervention on Pain and Anxiety Associated With Peripheral Intravenous Catheter Placement in the Pediatric Setting A Randomized Clinical Trial, 6). Effectiveness of virtual reality on pain and anxiety management in cancer patients, Literature review. So thus, the involvement of all parties is needed to improve distraction techniques using Virtual Reality during intervention so that it is hoped that it can reduce the pain scale in children according to standard care in every hospital that gets invasive procedures. In conclusion, the Virtual Reality distraction technique has or is very influential on the condition of the child to be carried out or to receive medical procedures. Keywords: School Children, Hospitalization, Pain and Cas Levels, Virtual Reality